Desain Single Passive Tuned Filter untuk Meredam Harmonisa pada Transformator 1000 kVA - Prima Abdi Saputra; Zulfatri Aini Efa; Nanda Putri Miefthawati (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2026)
The increasing use of non-linear loads in electrical distribution systems has caused harmonic distortion problems that can degrade power quality. Harmonics may increase transformer losses, reduce transformer capacity, decrease system efficiency, and increase operational costs due to power losses. This study aims to design a single passive tuned filter to mitigate harmonics in a 1000 kVA transformer at UIN Suska Riau. Data collection was conducted through direct measurements using a Power Quality Analyzer, while system validation was performed using ETAP simulation software. The measurement results showed that the Total Harmonic Distortion of Current (THDi) in several phases exceeded the IEEE 519-2014 standard limit, with the 3rd-order harmonic identified as the dominant harmonic component. Therefore, a single passive tuned filter was designed by determining the appropriate resistor, inductor, and capacitor parameters based on the dominant harmonic order. The results demonstrated that the proposed filter successfully reduced THDi values below the IEEE 519-2014 standard limit. In addition, the filter reduced transformer derating, minimized transformer losses, and decreased energy loss costs caused by harmonics. The ETAP simulation results were consistent with the analytical calculations, confirming that the designed filter effectively improved power quality and transformer performance in the electrical distribution system.